Analysis of Endometriosis Using Energy Dispersive X-ray Fluorescence Spectrometry - Ekinci, N.; Ingeç, M.; Dogan, B.; Agbaba, M.; Senemtasi, E. (Asian Journal of Chemistry, 2011)
Energy dispersive X-ray fluorescence method have been used to determine concentrations of the elements present in endometriosis. X-ray spectra have been collected using a Si(Li) detector with Camberra DSA-1000 desktop spectrum analyzer and Am241 and Fe55 annular radiactive sources. The energy resolution of the spectrometer is 160 eV at 5.9 keV. It has been seen from experimental results that there are general chlorine, potassium and calcium-enrichment. The relative errors for Am241 and Fe55 radioactive sources were found 2-6 %. Energy dispersive Xray fluorescence technique has been successfully applied for the determination of elements present in endometriosis.